Histopathological Changes in Structure of Kidney Under the Consumption of Energy Drinks in Rats (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The study aims to assess the impact of various doses of  ZIP on kidney of rats. Forty five rats were assigned  to three groups (15  animals/group). Control group (1) received standard diet and water, group 2 and group 3 received daily oral doses of 10 ml/kg/rat and 20 ml/kg/rat of the energy drink (ZIP) respectively for 30 days. Under light microscope no tissue changes were seen in kidney of control group. In group 2 ZIP causes vacuolar degeneration as well as coagulative necrosis  of  renal epithelium,  vascular  congestion  in  the  glomeruli  and  in  the interstitial  part  of  the  kidney.    In group 3 ZIP leads to more atrophic glomeruli,  massive necrosis  of  renal  tubular  epithelium,  marked  vascular dilatation and  congestion in  the interstitial tissue and degenerative changes of the  renal tubular epithelium. It is concluded that administration of red bull to rats for 30 days will affect the histological structure of kidney and this effect is a dose dependent.